Advanced Manufacturing Methods for High-Dose Inhalable Powders - Haia A. Al-Assaf; Sofia A. Papadimitriou; Ayesha Rahman; Raj Badhan; Afzal R. Mohammed (Pharmaceutics)
Pulmonary drug delivery is governed by three main categories of forces: interparticle forces in the powder formulation, the dispersion forces during inhalation by the device, and deposition forces in the lungs. The interaction between fine inhalable powder particles of the active ingredient is governed by various types of forces, such as capillary forces, electrostatic forces, and van der Waals forces. The different types of inter-particle interactions influence the balance between powder dispersibility and agglomerate stability. The high level of cohesion forces arising from high surface energy of very fine powder hinders powder flowability, leading to issues of agglomeration. Therefore, there is a critical need for advanced manufacturing techniques to overcome the challenges of handling and manufacture of fine cohesive particles, particularly high-dose powders for inhalation. This review will focus on the challenges facing the formulation process of very fine inhalable powder, the various types of existing particle engineering techniques for high-dose powder inhalers, and the characterization techniques employed to analyse the powder characteristics required to meet the acceptance criteria of inhalable preparations.